GLOBALIZATION AND INSECURITY IN NORTH CENTRAL NIGERIA: AN EVALUATION OF FARMER-HERDERS CONFLICT AND NATIONAL SECURITY IN NIGERIA. - T. Fabian , Hian, (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2023)
This study examined globalization and insecurity in North Central Nigeria with specific reference to farmer-herders conflict and National Security in Nigeria. The researcher used primary data from a sample of 300 respondents obtained by the use of a structured questionnaire from the study areas. Inferential descriptive statistics such as linear regression analysis was used to examine the effect of the independent variables on the dependent variable of the study. The hypotheses of the study were tested using the probability value of the estimates. The result of the study shows that food insecurity in the study area has a negative effect on national security in North Central Nigeria and the effect is not statistically significant (p>0.05) and but in line with a priori expectation. Displacement of farmer on farmers has a negative on national security in North Central Nigeria and the effect is not statistically significant (p>0.05) but in line with a priori expectation. A negative relationship exist between loss of life as occasioned by farmers-herders conflict national security in North Central Nigeria and the effect is not statistically significant (p>0.05) but in line with a priori expectation. This means that a unit increases in loss of life will result to a corresponding decrease in national security in North Central Nigeria by margin of 20.8%. It was concluded that food security, displacement of farmers and losses of lives as occasioned by farmers-herders crisis all have a negative effect on national security in North Central Nigeria. It was recommended among others that the farmer-herders conflict could be ameliorated if government act proactively by establishment of ranches so that they will be a reduction of conflict and thus improvement in food security in the region